1995
DOI: 10.1099/0022-1317-76-5-1117
|View full text |Cite
|
Sign up to set email alerts
|

African swine fever virus gene j13L encodes a 25-27 kDa virion protein with variable numbers of amino acid repeats

Abstract: The African swine fever virus (ASFV)j 13L gene encodes a 177 amino acid protein (19.0 kDa) with a putative transmembrane domain between residues 32 and 52. There is a potential signal peptide cleavage site at residue 54 and several possible motifs for phosphorylation and myristylation. Rabbit antisera raised against a synthetic peptide from the C terminus of the j 13L ORF identified proteins of 25-27 kDa in cells infected with a recombinant vaccinia virus expressing the j 13L ORF, in ASFV-infected cells and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 22 publications
3
40
0
Order By: Relevance
“…Immunoblotting with purified Ig against a C-terminal peptide from the j13L protein (Sun et al, 1995) identified proteins of 25, 27 and 23 kDa in cells infected with ASFV, vSJ1 and vSJ2, respectively, but not in wt VV-infected cells (Fig. 1 b).…”
Section: Construction Of Rvvs Expressing the Asfv J13l Proteinmentioning
confidence: 99%
See 4 more Smart Citations
“…Immunoblotting with purified Ig against a C-terminal peptide from the j13L protein (Sun et al, 1995) identified proteins of 25, 27 and 23 kDa in cells infected with ASFV, vSJ1 and vSJ2, respectively, but not in wt VV-infected cells (Fig. 1 b).…”
Section: Construction Of Rvvs Expressing the Asfv J13l Proteinmentioning
confidence: 99%
“…To examine expression of the j13L protein, BSC-40 cells were infected with vSJ1, vSJ2 or wt VV, and as a control pig macrophages, prepared as described previously (Sun et al, 1995), were infected with ASFV Malawi LIL20\1. Immunoblotting with purified Ig against a C-terminal peptide from the j13L protein (Sun et al, 1995) identified proteins of 25, 27 and 23 kDa in cells infected with ASFV, vSJ1 and vSJ2, respectively, but not in wt VV-infected cells (Fig.…”
Section: Construction Of Rvvs Expressing the Asfv J13l Proteinmentioning
confidence: 99%
See 3 more Smart Citations